Mother Tongue Phonological Interference in College Students’ English Pronunciation: A Qualitative Analysis of Speaking Task Video - Yousef Bani Ahmad (Journal of Innovative and Creativity, 2025)
This study aims to identify the patterns of mother-tongue phonological interference that appear in the English pronunciation of non–English major students through the analysis of speaking task videos. Using a descriptive qualitative approach, the research focuses on segmental and suprasegmental deviations, particularly changes in vowel and consonant sounds as well as word stress patterns influenced by the phonological system of the first language. Data were obtained from ten student videos and analyzed using phonological theory. The findings indicate that phonological interference occurs consistently in several major forms, namely: (1) the substitution of consonant sounds that do not exist in Indonesian, such as /v/→/f/, /ð/→/d/, and /θ/→/t/; (2) the failure to reduce schwa vowels, resulting in all vowels being pronounced fully; (3) the simplification of diphthongs into monophthongs, such as /oʊ/→/o/ and /aɪ/→/e/; (4) the deletion of final consonants and simplification of consonant clusters; and (5) stress shifts caused by the syllable-timed rhythmic pattern of Indonesian. These deviations demonstrate a strong influence of the mother tongue’s phonology on the production of English utterances, affecting the naturalness and intelligibility of pronunciation. This study provides an important contribution to pronunciation teaching, particularly in developing learners’ phonological awareness. By understanding the characteristics of the first language sound system and its differences from English, instructors can design more effective articulatory and prosodic training strategies to significantly improve students’ pronunciation skills